Asymmetric poly (vinyl alcohol)/Schiff base network framework hybrid pervaporation membranes for ethanol dehydration. (5th January 2022) - Zhao, Dan; Li, Meisheng; Jia, Mingmin; Zhou, Shouyong; Zhao, Yijiang; Peng, Wenbo; Xing, Weihong
Graphical abstract: Highlights: SNW-1 (COFs) with microporous structure and high nitrogen content was synthesized. SNW-1 with large mounts water transport channels was incorporated into PVA matrix. The PVA-SNW-1 membranes could overcome the trade-off effect effectively. The new membranes exhibited excellent thermal and long-term operating stabilities. Abstract: Asymmetric pervaporation mixed matrix membranes (MMMs) were constructed by incorporating a low-density Schiff base network framework (SNW-1) into a relative high-density poly(vinyl alcohol) (PVA) matrix. A large amount of SNW-1 nanoparticles enriched onto the membrane surface due to the buoyancy effect. Meanwhile, a small amount of SNW-1 nanoparticles still remained in PVA body due to the slow solvent evaporation. This asymmetric distribution in PVA body gives the membrane three larger advantages. Firstly, the surface enrichment of SNW-1, which contains many nitrogen-groups, enhances membrane's hydrophilicity and swelling resistance significantly. Secondly, the interfacial interactions could exit between SNW-1 and PVA matrix, thereby improving the membrane's mechanical stability and heat-resistance property. Thirdly, the SNW-1 nanoparticles with water-selective pore structures in PVA body or on membrane surfaces could all increase membrane separation performances. As a result, for 90 wt% ethanol aqueous, the prepared MMMs containing only 1.5 wt% SNW-1 owned a separation factor of 751 and a total flux of 254 g/m 2 h. Furthermore, the MMMs exhibited an excellent long-term operating stability. After running 120 h at 75 °C, the total flux and separation factor still remained at their initial values. The prepared MMMs show a potential for ethanol or other alcohols dehydration applications.